2013
DOI: 10.1002/cbdv.201100256
|View full text |Cite
|
Sign up to set email alerts
|

Natural Friedelanes

Abstract: This review covers the occurrence and biological activities of all natural friedelane triterpenoids found between 1977 and March 2011. The biogeneses of dimeric friedelanes and several rearranged friedelanes are discussed. The pharmacological properties of representative compounds, including celastrol and correolide, have also been compiled, on the basis of 344 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 320 publications
0
13
0
2
Order By: Relevance
“…While sesquiterpene polyesters have been isolated primarily from fruit, sesquiterpene pyridine alkaloid macrolides are present in several organs, and their concentrations are often fairly high in roots (Gao et al, 2007). Friedelane triterpenoids are a third prominent class of specialized metabolites in the Celastraceae (more than 50 structures; Shan et al, 2013), and our searches indicated that 26 different friedelanes have been described in Tripterygium.…”
Section: Development Of Combined Hplc-ms and Nmr Spectral Libraries Fmentioning
confidence: 80%
“…While sesquiterpene polyesters have been isolated primarily from fruit, sesquiterpene pyridine alkaloid macrolides are present in several organs, and their concentrations are often fairly high in roots (Gao et al, 2007). Friedelane triterpenoids are a third prominent class of specialized metabolites in the Celastraceae (more than 50 structures; Shan et al, 2013), and our searches indicated that 26 different friedelanes have been described in Tripterygium.…”
Section: Development Of Combined Hplc-ms and Nmr Spectral Libraries Fmentioning
confidence: 80%
“…Of the 27 compounds detected from our workflow, 18 were annotated as sterol‐like, eight were annotated as terpene‐ or terpenoid‐like, and one did not match well to any compound type in the metabolite databases used. A wide diversity of terpenes, including numerous unique types, have been described from the Celastraceae (Shan et al ., ). The bioactivity of terpenes in the Celastraceae has been studied within certain species given their potential application as painkillers, cancer treatments, anti‐HIV agents, diabetes treatments, and antidepressants (Shan et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Five compounds annotated as terpenes were found in high abundance in Cassine schinoides , one in Pseudocatha mandenensis , one in Peripterygia marginata, and one found in both Pseudocatha mandenensis and Cheiloclinum hippocratedides (Figs ) . As with sterols, terpenes are commonly found in the Celastraceae (Shan et al ., ). It appears that the species Cassine schinoides , Pseudocatha mandenensis, and Cheiloclinium hippocrateoides have not been part of any published phytochemical work on terpenes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…222 A review of naturally occurring friedelanes, isolated between 1977 and March 2011 has been published. 301 Ovalifolones A 556 and B 557, from Garcinia ovalifolia, 302 Clerodendrumic acid 624, from Clerodendrum glabrum, has also be reported with this stereochemistry. 337 The acetonide 625 is likely to be an artefact from chromatography of the extract of Rhododendron hainanense.…”
mentioning
confidence: 95%